Performance and Participatory Evaluation of Improved Tomato (Solanum lycopersicum L.) Varieties in North-Gondar Zone, Gondar, Ethiopia - Kassa, Azeze Wubie; Mohamed, Hayat Yasin; Edeshew, Asemamaw Bidru; Akililu, Endalckachew; Worku, Bidgye Wubie (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted from December to March during 2020 and 2021 cropping irrigation season at Metema and Belesa, Ethiopia to evaluate tomato varieties' adaptability, yield potential, and farmer preferences. The performance evaluation and farmer preferences of ten tomato varieties were conducted on farmers and research fields in two locations in the north Gondar zone, Gondar-Ethiopia, over two off seasons. Agronomic data, as well as farmer preferences for the varieties, were collected and analyzed using R statistical software, Agricola. R Package, Version, 1–2, and pair-wise ranking, respectively. The performance of varieties had shown significant variation between varieties and across locations. The results in the Metema district revealed that there was a significant (p≤0.001)) difference between the varieties in all agronomic parameters except the number of fruits cluster-1. Woyeno (30.60 t ha-1), Roma VF (30.37 t ha-1), Chali (29.31 t ha-1), and Cochoro (29.02 t ha-1) varieties produced significantly more marketable fruit. In a pair-wise ranking of farmer preferences, Chali (56), Cochoro (50), were chosen first and second, respectively. In the Belesa district, the non-significant difference in mean marketable fruit yield of tomato varieties ranged from 22.76 to 25.28 t ha-1. However, a pair-wise ranking of farmers' preferences revealed that ARP tomato (96) and Cochoro (96) ranked first and second, respectively. As a result of the agronomic data and farmer preferences, Cochoro and Chali varieties for Metema Districts and Cochoro and ARP tomato varieties for Belesa district will recommended for further scale-out the tested areas and similar agro-ecological areas.